Coupling the effect of mixed valence states and facet reorientation in cerium doped tungsten oxide for PEC water splitting: An insight via band alignment and DFT calculations - Sial, Qadeer Akbar; Ali, Rana Basit; Safder, Usman; Seo, Hyungtak (International Journal of Hydrogen Energy, 2025)
Tungsten oxide (WO3) is a key photoanode for the photoelectrochemical water splitting (PEC) application; however, it comes with the challenges of lower efficiency and larger photogenerated charge recombination. Oxygen vacancies are always favorable, up to some extent, to hinder this critical issue. In this study, we synthesized cerium (Ce) doped monoclinic WO3 with tuning of its work function along with the suitable band edge position for the PEC water splitting applications. Moreover, it was observed that the crystal phase was changed by a certain doping of Ce to {002} plane with 1D morphology, which in turn alters conduction band position as well as the Fermi energy level. The WO3 with 0.49 at % of cerium doping showed a record photocurrent up to ∼2.48 mA cm−2 1.23V vs. RHE as compared to the undoped WO3, which exhibited 1.53 mA cm−2 at 1.23V vs. RHE. It was observed that the WO3 with 0.49 at % of cerium doping showed charge separation efficiency up to ∼79% as compared to the undoped WO3 sample, which showed only 20%, which is one of the reasons for this elevated performance of the doped sample. Overall, the results indicate that Ce doping is beneficial for WO3 PEC applications and further it was confirmed by the DFT calculations as well.
Keywords: Cerium doping; Cerium-doped; DFT; DFT calculation; Doping criteria; Oxygen vacancy tuning; PEC water splitting; Tungsten oxide; Undoped WO; Water splitting; DFT; Doping criteria; Oxygen vacancies tuning; PEC water splitting; WO3